Análise do Grau de Aderência à Lei de Responsabilidade Fiscal e à Lei de Acesso à Informação nos Municípios do Estado do Rio Grande do Sul com Mais de 50 Mil Habitantes - Élida Elis Michel Vieira (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
The transparency in Applied Accounting to the Public Sector seeks to provide information which allows the citizens to have access to their rights. The objective of this research is to analyse the transparency degree in cities of Rio Grande do Sul with more than fifty thousand inhabitants based on the Fiscal Responsibility Law (FRL) – which aims the responsibility in fiscal management and on the Information Assessment Law (IAL) – which prompts the social control. As far as for the methodological procedures, this is classified as a quantitative, qualitative and documental research whereas, during the months of September and October of 2014, conformity indicators were used with the both laws mentioned in order to collect information available by the 40 cities of the State with more than 50 thousand inhabitants – which offered the Transparency Portal on the internet. The results gained show that much of the relevant information concerning budget and budget execution has not been presented as well as the lack of clarity and quality criteria when available. The Southeast Mesoregion of Rio Grande do Sul brought up the highest degree of transparency, with the Average General Conformity Index equaling 75,56%. However, the Southeast Mesoregion Sudoeste of Rio Grande do Sul – with the Average General CI of 51,11%, ended up being the least transparent one. Regarding the FRL, the least shown information was the Prior Report. As for the IAL, the acessibility query was the least punctuated by the counties. Therefore, it was observed that fiscalization is still missing when the laws compliance was required, making it difficult for the citizens to get public information, as well as their active participation on social control process.